Combination therapy using scoring and sirolimus drug-coated balloons during lower limb endovascular revascularization for chronic limb threatening ischaemia: A case series. (March 2022) - Bong, Tiffany SH; Yap, Charyl JQ; Soon, Shereen XY; Tang, Tjun Y
The aim of this case series was to document our early experience using combination therapy with UltraScore ™ Focused Force percutaneous transluminal angioplasty balloon (BD Interventional, New Jersey, US) and Selution Sustained Limus Release (SLR) ™ (M.A. MedAlliance SA, Nyon, Switzerland) sirolimus-coated balloon catheter for anti-restenotic drug elution, in the setting of multifocal high-grade stenosis for chronic limb threatening ischaemia. Our anecdotal experience was that preparing the lesion with scoring balloon and then using sirolimus drug-eluting balloon may have synergistic effect when used in tandem, especially in the setting of calcified arterial lesions, where the scoring wires may achieve deeper clefts within the atheromatous plaque to allow better drug absorption into the arterial wall. We report two cases with high-grade multifocal stenosis affecting the superficial femoral and anterior tibial arteries, respectively. Combination therapy using the scoring balloon to first prepare the lesion followed by sirolimus elution achieved technical and procedural success in both cases and a 100% 30-day primary patency. There were no complications related to flow-limiting dissections, vessel perforation or acute recoil. However, whether this combination therapy leads to better primary vessel patency with longer freedom from target lesion revascularization in the medium term remains to be determined.